Nomogram for second trimester corpus callosum measurements: are nomograms reliable? - Alemdaroğlu, Songül; Baran, Şafak Yılmaz; Doğan Durdağ, Gülşen; Yüksel Şimşek, Seda; Çoban Şerbetçioğlu, Gonca; Kalaycı, Hakan (Perinatal Medicine Foundation, 2020)
Objective: To define normal values of second trimester fetal corpus callosum (CC) length and width in a low-risk population and to compare the presented nomograms to those in the literature. Methods: The prenatal records of singleton fetuses who underwent second trimester anomaly screening at 18.0-22.0 weeks of pregnancy were retrospectively analyzed for CC width and length. A total of 710 fetuses, whose anomaly scans were completely normal, were included in the study. The correlations between CC and biparietal diameter (BPD), head circumference (HC) and gestational age (GA) were evaluated. Results: At 18.0-22.0 weeks of pregnancy, the mean CC length was 19.7±2.8 mm, while the mean CC thickness was 1.98±0.4 mm. In assessment of the correlations between the CC length and thickness values and the HC, BPD and GA values by Pearson's correlation coefficient, there was a stronger correlation between the CC length measurements and the BPD, HC and GA values (r=0.233 vs r=0.505, p<0.001). Conclusion: Assessment of the presence of corpus callosum as well as its length and thickness during routine fetal anomaly evaluation may be important owing to the relationship between corpus callosum measurements and certain neurological disorders. Studies indicate that populations should create their own nomograms due to different values reported in the literature.